Drug-specific risk of severe QT prolongation following acute drug overdose. (1st December 2020) - Campleman, Sharan L.; Brent, Jeffery; Pizon, Anthony F.; Shulman, Joshua; Wax, Paul; Manini, Alex F.
Abstract: Background: Severe QT prolongation (SQTP) has been identified as a strong predictor of adverse cardiovascular events in acute drug overdose, but drug-specific causes of SQTP in the setting of acute drug overdose remain unclear. We aimed to perform the most definitive study to date describing drug-specific risk of SQTP following acute drug overdose. Methods: This was a prospective multicenter cohort study at >50 hospital sites across the US using the ToxIC Registry between 2015 and 2018. Inclusion criteria were adults (≥18 years) receiving medical toxicology consultation for acute drug overdose. The primary outcome was SQTP, which was defined using the computer automated Bazett QT correction (QTc) on the ECG with the previously validated cut point of 500 milliseconds. Mean difference in QTc was also calculated for specific drugs. Drugs associated with SQTP were analyzed using multivariable logistic regression to control for known confounders of QT risk (age, sex, race, cardiac disease). Results: From 25, 303 patients screened, 6473 met inclusion criteria with SQTP occurring in 825 (13%). Drugs associated with increased adjusted odds of SQTP included Class III antidysrhythmics (sotalol), sodium channel blockers (amitriptyline, diphenhydramine, doxepin, imipramine, nortriptyline), antidepressants (bupropion, citalopram, escitalopram, trazodone), antipsychotics (haloperidol, quetiapine), and the antiemetic serotonin antagonist ondansetron. Conclusions: This large US cohort describes drug-specific risk of SQTP following acute drug overdose. Healthcare providers caring for acute drug overdoses from any of these implicated drugs should pay close attention to cardiac monitoring for occurrence of SQTP.